Question
upstudy study bank question image url

Solve the following equation completely. There are 3 answerboxes listed. \( x^{3}+2 x^{2}-2 x-4=0 \)

Ask by Rowe Moreno. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: - x = -2 - x = √2 - x = -√2

Solution

We start with the equation:   x³ + 2x² - 2x - 4 = 0 Step 1. Look for a rational root using the Rational Root Theorem. Test x = -2:   (-2)³ + 2(-2)² - 2(-2) - 4 = -8 + 8 + 4 - 4 = 0 So, x = -2 is a root. Step 2. Factor the polynomial by dividing by (x + 2). Dividing:   x³ + 2x² - 2x - 4 ÷ (x + 2) Use synthetic division with -2:   Coefficients: 1 2 -2 -4   Bring down 1.   Multiply 1 by -2 = -2; add to 2 gives 0.   Multiply 0 by -2 = 0; add to -2 gives -2.   Multiply -2 by -2 = 4; add to -4 gives 0. The quotient is: x² + 0x -2, which simplifies to x² - 2. Step 3. Solve the quadratic factor:   x² - 2 = 0  ⟹  x² = 2  ⟹  x = √2 or x = -√2 Thus, the complete solution set is: Answerbox 1: x = -2 Answerbox 2: x = √2 Answerbox 3: x = -√2

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( x^{3}+2 x^{2}-2 x-4=0 \), let's first look for possible rational roots using the Rational Root Theorem. Testing small integers, we find that \( x = 1 \) is a root. Now we can perform synthetic division to divide the polynomial by \( x - 1 \): ``` 1 | 1 2 -2 -4 | 1 3 1 -------------------- 1 3 1 -3 ``` This gives us the quotient \( x^2 + 3x + 4 \) and a remainder of \( 0 \). Thus, we can factor our original polynomial as: \[ (x - 1)(x^2 + 3x + 4) = 0 \] Next, we need to solve the quadratic \( x^2 + 3x + 4 = 0 \) using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Here, \( a = 1, b = 3, c = 4 \): \[ x = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 1 \cdot 4}}{2 \cdot 1} = \frac{-3 \pm \sqrt{9 - 16}}{2} = \frac{-3 \pm \sqrt{-7}}{2} \] This gives us complex roots: \[ x = \frac{-3}{2} \pm \frac{\sqrt{7}}{2}i \] Thus, the complete list of solutions for the equation \( x^{3}+2 x^{2}-2 x-4=0 \) is: 1. \( x = 1 \) 2. \( x = \frac{-3}{2} + \frac{\sqrt{7}}{2}i \) 3. \( x = \frac{-3}{2} - \frac{\sqrt{7}}{2}i \) So, the complete answer boxes will be: 1. \( 1 \) 2. \( \frac{-3}{2} + \frac{\sqrt{7}}{2}i \) 3. \( \frac{-3}{2} - \frac{\sqrt{7}}{2}i \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy